Poorly-Differentiated Signet-Ring Cell Carcinoma of the Ampulla of Vater: Report of a Rare Malignancy - Acharya, Metesh Nalin; Panagiotopoulos, Nikolaos; Cohen, Patrizia; Ahmad, Raida; Jiao, Long R (JOP. Journal of the Pancreas, 2013)
Context Signet-ring cell carcinoma (SRCC) of the ampulla of Vater is a very rare clinical entity, which is infrequently reported in medical literature. Case report A 78-year-old woman was admitted with jaundice, pruritus and postprandial vomiting. Abdominal ultrasound and computed tomography scanning demonstrated gross dilatation of the common bile and pancreatic ducts with gallbladder calculi. Endoscopic retrograde cholangiopancreatography suggested a duodenal tumour at the ampulla. The patient underwent Whipple’s procedure with cholecystectomy. Immunohistopathological examination confirmed poorly-differentiated SRCC of the ampulla of Vater. The tumour had infiltrated the duodenal muscularis propria and pancreatic parenchyma, but local lymph nodes were clear (T3N0M0). The patient was disease-free at 6-month follow-up. Conclusions We here report a case of poorly-differentiated SRCC of the Ampulla of Vater. The majority of patients with such tumours undergo pancreaticoduodenectomy, which affords good outcomes in early disease. However, owing to the rarity of cases, the exact prognosis of ampullary SRCC remains as yet undetermined. Image: Axial slice of the head of the pancreas.